TEKNIK BAWAH-ATAS UNTUK MEMPERMUDAH PENYELESAIAN DEDUKSI ALAMI DENGAN SISTEM GENTZEN - Dwijono, Djoni (Proceedings of KNASTIK, 2012)
Natural Deduction settlement in the realm of propositional logic, normally resolvedthrough top-down techniques, which means that the deduction starts from an expressionthat has been given and or with the assumption, then the rules of certain inferenproduce the next process is called derivation. This method done continuously until thelogical expression to be proved as the results are really materialized.Top-downapproach has certain difficulties not easily solved the difficulty to find an expressionthat became the beginning of proof or of the assumptions used. The difficulty isattempted facilitated by the completion of proof is reversed by bottom-up techniques.Verification process should start from the proved to find beginning of the proof.Toexplain the process of bottom-up approach, in this paper will be given an example onone of the Natural Deduction proof by Gentzen system.